2023
DOI: 10.1002/gcc.23116
|View full text |Cite
|
Sign up to set email alerts
|

A novel colony‐stimulating factor 1 (CSF1) translocation  involving human endogenous retroviral element in a tenosynovial giant cell tumor

Abstract: Tenosynovial giant cell tumors (TSGCTs) are rare tumors arising in tendons or the synoviae of joints and bursae. The localized type is benign while the diffuse type shows expansive growth leading to greater morbidity and is therefore considered locally aggressive. Typical recurrent chromosomal aberrations are found in the majority of TSCGT and the CSF1 gene is frequently involved. In this article, we describe a newly identified gene fusion mediated by an inversion in a case of diffuse TSGCT.Multicolor-fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…The vast majority of fusions identified in MPS studies are non-recurring, and, as such, have been identified as stochastic events [19]. While large-scale MPS efforts have been enormously productive in identifying fusion break points, novel oncofusions and their acting mechanisms are still being identified from MPS data at an accelerating pace [85][86][87][88][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120], and while multiple fusion databases are available [64,121,122], a centralized and standardized hub akin to, for example, IntAct [123] for interaction data or UniProt [124] for protein information has yet to emerge.…”
Section: Protein-level Analysis Of Oncofusionsmentioning
confidence: 99%
“…The vast majority of fusions identified in MPS studies are non-recurring, and, as such, have been identified as stochastic events [19]. While large-scale MPS efforts have been enormously productive in identifying fusion break points, novel oncofusions and their acting mechanisms are still being identified from MPS data at an accelerating pace [85][86][87][88][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120], and while multiple fusion databases are available [64,121,122], a centralized and standardized hub akin to, for example, IntAct [123] for interaction data or UniProt [124] for protein information has yet to emerge.…”
Section: Protein-level Analysis Of Oncofusionsmentioning
confidence: 99%